Privatized religiosity revisited: Building an authenticity model of individual–church relations - Pessi, Anne Birgitta (Social compass, 2013)
A majority of scholars agree that late-modern religiosity is characterized by ‘privatization’, particularly in Western Europe. However, even a general picture reveals that the privatization thesis is both verified and contradicted by aspects of the European religious scene. Particularly, since religion de facto is a social phenomenon, what is the meaning of a community to an individual with privatized religiosity? This is the focus of the author. The data include 17 in-depth interviews, which were analyzed with grounded theory methodology. The analysis generates a novel authenticity model of individual−church relations which consists of the interplay between three elements: experiences (especially rites, traditions, and emotions), values (both expectations of the church and personal values in relation to the church), and truth (frameworks for reflection, supply of religious activities, clear standpoints, and space for individuality) – as well as authenticity, which is present in all three.